The Unconventional Approach to Evidence in Criminal Trials - Aghenitei, Mihaela (Acta Universitatis Danubius. Juridica, 2023)
There is an indissoluble connection between the evidence and the means of proof, since the evidence can only be used if it is obtained through the means of proof provided by the law, a connection that can cause one to be confused with the other. The legal means of evidence by which the evidence in the criminal process is obtained presuppose certain concrete practical ways that the judicial bodies must resort to for their legal administration. These methods are called evidentiary procedures. The possibility given by the legislator to the judicial bodies in the sense of the administration of evidence in the criminal process by means of evidence other than those provided by way of example demonstrates a flexible, modern legal thinking, adapted to social realities, in the service of finding the truth in the criminal process, distinguished from the one addressed in the old Criminal Procedure Code. The freedom of evidence conditioned by the legality of obtaining it, in the context of continuous and implicit technological changes in the means of committing crimes, represents an evolution from a legal point of view, a useful and flexible tool available to judicial bodies to find out the truth.